Fatwa MUI Nomor 83 Tahun 2023 Terkait Pemboikotan Produk Israel (Tinjauan Aspek Ekonomi, Sosial Dan Politik) - Syam, Syafruddin (Legal Standing : Jurnal Ilmu Hukum, 2025)
This study aims to analyze the implementation of the Indonesian Ulema Council (MUI) Fatwa Number 83 of 2023 concerning the boycott of Israeli products, with a focus on its impact in North Sumatra Province from economic, social, and political aspects. The research method used in this study is qualitative using a legal sociology approach. The data sources used are primary data and secondary data with data collection methods, namely literature review and interviews. The results of the study obtained indicate that the MUI fatwa Number 83 of 2023 concerning the boycott of Israeli products, viewed from an economic aspect, has the potential to reduce the income of Israeli companies that rely on exports to international markets, including Indonesia. From a social aspect, this boycott is a manifestation of concern for the suffering of others and support for their struggle. From a political aspect, this fatwa has several implications, specifically support for Palestine. This study is expected to contribute to the understanding of the interaction between ulama fatwas, public policy, and public response in the context of sensitive international issues.